Public Space in the Late Antique City (2 vols.) - Lavan, Luke, author.
1 online resource.
Keywords: “This book investigates the nature of 'public space' in Mediterranean cities, A.D. 284-650, meaning places where it was impossible to avoid meeting people from all parts of society, whether different religious confessions or social groups. The first volume considers the architectural form and everyday functions of streets, fora / agorai, market buildings, and shops, including a study of processions and everyday street life. The second volume analyses archaeological evidence for the construction, repair, use, and abandonment of these urban spaces, based on standardised principles of phasing and dating. The conclusions provide insights into the urban environment of Constantinople, an assessment of urban institutions and citizenship, and a consideration of the impact of Christianity on civic life at this time“--